Serum Markers Predicting Early Non-Responsiveness to Infliximab in Rheumatoid Arthritis: Tumor Necrosis Factor (TNF)-Alpha, TNFRII, and Interleukin (IL)-17 As Potential Indicators (Iraqi Journal of Medical Sciences, 2025)
Background:    Infliximab is a type of biologic medication used in the treatment of rheumatoid arthritis (RA) and other autoimmune conditions. While it can be highly effective for many patients, there are cases of early unresponsiveness to infliximab.Objective:    To investigate the predictive value of serum biomarkers, specifically tumor necrosis factor alpha TNF-), TNFRII, and interleuking-17 (IL-17), in identifying early non-responsiveness to infliximab in patients with RA. Methods: In this case-control study blood samples were obtained from 100 RA patients (50 responders and 50 non-responders) and 100 age and sex matched apparently healthy control. Serum levels of TNF-, TNFRII, and IL-17 were measured by enzyme-linked immunosorbent assay.Results: In patient group, the median serum level of (TNF-α and IL-17) were higher than those of control group with a significant difference. Additionally, the median serum levels of TNF-α, and IL-17 in non-responder patients were significantly higher than those in responder group. Although, there was a higher median level of TNFRII in non-responder patients, no significant differences were observed. TNFRII displayed a significant positive correlation with TNF-α. While IL-17 had a significant positive correlation with each of TNFRII and TNF-α.  ROC test revealed that TNF-α had 81% sensitivity and 74% specificity at a cut-off value of 78.4 ng/l, while TNFRII had 80% sensitivity and 77% specificity at 7.8 ng/ml, and IL-17 had 80% sensitivity and 71% specificity at a cut-off value of 46.91 ng/l.Conclusion: There was a positive association between elevated levels of TNF-α and IL-17 and early unresponsiveness to infliximab in RA patients. Keyword::    Rheumatoid Arthritis, TNF-α, TNFRII, IL-17.Citation: Fadhil ZJ, Abbas AA, Al-Osamai MH. Serum markers predicting early non-responsiveness to infliximab in rheumatoid arthritis: tumor necrosis factor (TNF)-Alpha, TNFRII, and interleukin (IL)-17 as potential indicators. Iraqi JMS. 2025; 23(1): 128-138. doi: 10.22578/IJMS.23.1.15